Language, Media and Globalization in the Periphery The Linguascapes of Popular Music in Mongolia - Dovchin, Sender (Routledge, 2018)
Drawing on data examples obtained from ethnographic fieldwork trips in Mongolia, a country located geographically, politically and economically on the Asian periphery, this book presents an example of how peripheral contexts should be seen ...